TANTANGAN KESEHATAN ANAK DI DESA: MENINJAU RENDAHNYA CAKUPAN IMUNISASI, STUNTING, DAN DAMPAK PROGRAM DESA SEHAT - Dinopawe, Asriaty (STIKES Pasapua Ambon, 2023)
Introduction: Child health in rural areas is an issue that requires serious attention, especially with low immunisation coverage, the high risk of stunting related to maternal education levels and family income, and village government efforts that need to be improved in implementing the Healthy Village Program. Through an in-depth understanding of children’s problems, concrete steps can be taken to improve the welfare of the next generation in rural communities. Methods: The method used in this study was literature review. The articles collected were qualitative and quantitative articles on the review of low immunisation coverage, stunting and the impact of village programs on children’s health. Results: Low immunisation coverage and family planning participation, family income has a 5 times higher risk of stunting and evaluation of the healthy village program is sufficient. Conclusion: Significant health challenges especially in Maternal and Child Health (MCH) programmes require increased preventive efforts, the importance of a holistic approach to and improvements need to continue.